THE GROWTH OF Asystasia gangetica (L.) subsp. Micrantha FERTILIZED WITH A MIXTURE OF GOAT MANURE AND GRAPE WASTE - I., Pasae,; Kusumawati, N. N. C.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2024)
Asystasia gangetica is a weed species that has good nutrient content as animal feed. This study aimed to determine the growth of Asystasia gangetica (L.) subsp. Micrantha fertilized with a mixture of goat manure and grape waste. This research was conducted in Sading Village, Mengwi District, Badung Regency, Bali Province for a period of 12 weeks. This study used a Completely Randomized Design (CRD) consisting of 6 treatments and 5 replications, namely; treatment A: no fertilizer, B: 100% grape waste, C: 100% goat manure, D: 75% goat manure + 25% grape waste, E: 50% goat manure + 50% grape waste and F: 25% goat manure + 75% grape waste. The variables observed include: plant height (cm), number of leaves (leaves), number of branches (branches), leaf color, leaf chlorophyll, and stem diameter (cm). The results of the study on the growth of Asystasia gangetica (L.) subsp. Micrantha fertilized with a mixture of goat manure and grape waste showed that the application of goat manure and grape waste was not significantly different (P>0.05) for all variables. In treatment C (100% goat manure) showed the highest results for all variables except the number of branches which showed the highest results in treatment F (75% goat manure + 25% grape waste) and stem diameter was the highest in treatment A (100% without fertilizer). Based on the results of the study, it can be concluded that the growth of Asystasia gangetica (L.) subsp. Micrantha is not influenced by the application of a mixture of manure and grape waste and a mixture of goat manure and grape waste has not been found to improve the growth of Asystasia gangetica (L.) subsp. Micrantha.